Understanding Volunteer Commitment through Self-Eficacy and Altruisme: Insight from the Indonesian Philanthropy Sector - Zahra, Firyal Syafa; Hidayati, Sri (Tauhidinomics: Journal of Islamic Banking and Economics, 2025)
Volunteers are a vital resource for sustaining philanthropic and non-profit organizations, yet not all maintain long-term engagement. High volunteer commitment is critical to ensuring continuous operations and impact. This study investigates the role of self-efficacy and altruism in shaping volunteers’ commitment, focusing on the Berdikari Foundation, an Indonesian community-based philanthropy active in the education sector. Using purposive sampling, 60 volunteers with a minimum of two years’ service and active event involvement participated in the survey. Data were analyzed using SEM-PLS. Findings reveal that both self-efficacy and altruism positively and significantly predict volunteer commitment, offering a multidimensional model that integrates these psychological factors. This research extends existing literature, which has largely focused on motivation and satisfaction, by highlighting self-efficacy and altruism as critical determinants of sustained engagement. Practical implications include designing volunteer management strategies that fosterconfidence, empathy, and prosocial values. Limitations include the single-organization sample, suggesting the need for broader studies across diverse philanthropic settings in Indonesia. Keywords: Volunteers’ commitment; self-efficacy; altruism; philanthropy